Education as an important aspect in the care of a patient with Chronic Obstructive Pulmonary Disease (COPD) - Agata Ulenberg; Grzegorz Ulenberg; Mirosława Felsmann; Marzena Humańska; Danuta Ponczek; Maria Dąbrowska (Kazimierz Wielki University, 2017)
Chronic Obstructive Pulmonary Disease is a disease that is characterized by persistent bronchial obstruction (by lowering FEV). This handicap shows progressive tendencies and is basically irreversible. Due to the number of deaths and deaths in the world, COPD is a huge challenge for the world of medicine. Having a basic knowledge of illness and treatment translates into more effective self-care, which reduces the risk of hospitalization and positively affects the quality of life.